2022
DOI: 10.1063/5.0128265
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality reduction of local structure in glassy binary mixtures

Abstract: We consider unsupervised learning methods for characterizing the disordered microscopic structure of supercooled liquids and glasses. Specifically, we perform dimensionality reduction of smooth structural descriptors that describe radial and bond-orientational correlations and assess the ability of the method to grasp the essential structural features of glassy binary mixtures. In several cases, a few collective variables account for the bulk of the structural fluctuations within the first coordination shell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
(146 reference statements)
0
13
0
Order By: Relevance
“…It was later demonstrated that more refined observables could be calculated [15] and combined with simpler models to capture the connection between statics and dynamics in glassy systems [16,17]. Similar results can be achieved even with information theory [18,19] and dimensionality reduction [19,20]. Recently, neural networks have also been used to find complex order parameters for glassy dynamics [21].…”
Section: Introductionmentioning
confidence: 80%
“…It was later demonstrated that more refined observables could be calculated [15] and combined with simpler models to capture the connection between statics and dynamics in glassy systems [16,17]. Similar results can be achieved even with information theory [18,19] and dimensionality reduction [19,20]. Recently, neural networks have also been used to find complex order parameters for glassy dynamics [21].…”
Section: Introductionmentioning
confidence: 80%
“…The relationship between the Al local structure and NMR parameters was examined as a function of the degree of symmetry in the Al coordination structure. The degree of symmetry for the Al polyhedron was investigated using spherical harmonic functions, which are useful for quantitating the local symmetry of liquid and amorphous materials. The polyhedral structure formed with Al and O within the first coordination sphere was extracted from the AIMD-derived structure. The longest Al–O bonds in the extracted polyhedron were aligned to be parallel to the z axis through a rotational operation, and the polyhedron was rotated such that the second longest Al–O bond in the polyhedron was parallel to the xz -plane.…”
Section: Resultsmentioning
confidence: 99%
“…structural indicators that predict dynamical properties in densely disordered (near-)equilbrium systems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. These findings firmly establish a correlation between local structure and the propensity of passive particles to move in a crowded environment.…”
mentioning
confidence: 88%